2020
DOI: 10.1042/bcj20200533
|View full text |Cite
|
Sign up to set email alerts
|

The thiol oxidation-based sensing and regulation mechanism for the OasR-mediated organic peroxide and antibiotic resistance in C. glutamicum

Abstract: Corynebacterium glutamicum, an important industrial and model microorganism, inevitably encountered stress environment during fermentative process. Therefore, the ability of C. glutamicum to withstand stress and maintain the cellular redox balance was vital for cell survival and enhancing fermentation efficiency. To robustly survive, C. glutamicum has been equipped with many types of redox sensors. Although cysteine oxidation-based peroxide-sensing regulators have been well described in C. glutamicum, redox se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…glutamicum (Si et al, 2020). Moreover, M. tuberculosis Rv2466c was validated to promote mycobacterial resistance to oxidative stress (Rosado et al, 2017).…”
Section: Ncgl0018 Null Mutant Was Sensitive To Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…glutamicum (Si et al, 2020). Moreover, M. tuberculosis Rv2466c was validated to promote mycobacterial resistance to oxidative stress (Rosado et al, 2017).…”
Section: Ncgl0018 Null Mutant Was Sensitive To Oxidative Stressmentioning
confidence: 99%
“…S5). Recently, Si et al (2020), found that NCgl0018 was also one of the main targets of OasR by microarray analysis, which is strongly linked to the oxidative stress response in C. glutamicum. Therefore, we further detected OasR's regulatory capacity for NCgl0018.…”
Section: Ncgl0018 Expression Was Regulated By Sigh and Oasr In C Glutamicummentioning
confidence: 99%
See 1 more Smart Citation
“…Logically, cells exposed to diamide will downregulate OsnR, due to transcriptional repression of the osnR gene by its own protein, thereby de-repressing the stressresponsive genes. In addition, changes in cellular redox status can cause structural modification of the OsnR protein through cysteine residues, resulting in changes in the activity and functional properties of the protein, as such mechanism was proposed for other regulators, such as CosR (C49 and C62), MsrR (C62), OasR (C95), OhsR (C125), OxyR (C199 and C208), RosR (C92), and QorR (C17) [25][26][27][28][29][30][49][50][51]. The OsnR protein has two cysteine residues (C2 and C10) at the N-terminus, and these residues may function as a thiol-based redox switch to respond to cellular redox status.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many of these proteins contain cysteine residues in a configuration that may respond to cellular redox signals, thereby regulating cognate stressresponsive genes. These cysteine-containing regulators in C. glutamicum include WhcE and WhcA [22,23], OxyR [8,24], OhsR [25], RosR [26], MsrR [27], CosR [28], QorR [29], OasR [30], and OsrR [31]. In addition, along with the master regulator SigH [32,33], multiple regulatory proteins also participate directly or indirectly in the regulation of oxidative-stress responses [34,35].…”
Section: Introductionmentioning
confidence: 99%